Histone methylations in the developing central nervous system and in neural tube defects - Villarreal, Alejandro (2018)
Understanding central nervous system genesis is of crucial relevance to decode different human diseases such as microcephaly or neural tube defects, which arise from incorrect developmental processes. Epigenetic mechanisms regulate gene expression in a spatio-temporal manner and are implicated in diverse cellular actions one of which is cell differentiation. Therefore, the study of these mechanisms is of great relevance in the context of development and disease. In this article, we will review histone methylations as epigenetic modification and how they impact on gene expression and cell differentiation in central nervous system development and neural differentiation. Further, we will discuss an emerging link between histone methylation in the etiology of neural tube defects. We will specifically highlight the role of the disruptor of telomeric silencing like 1 (DOT1L) and histone H3 lysine 79 methylation (H3K79me), which is an unusual histone modification with implication for proper central nervous system development.